A review on somaclonal variation of oil palm (Elaeis guineensis Jacq.) / Nur Aliyana Bahrum - Bahrum, Nur Aliyana (Faculty of Plantation and Agrotechnology, 2019)
Cultivation of oil palm (Elaies guineensis Jacq.) has been started with the main objective is to achieve high yield production. A research and development on tissue culture already started since early 1970. The early succeed of plantlets production become inspiration for many oil palm organizations to explore in vitro propagation technique. Several micro propagation techniques such as callogenesis, organogenesis and somatic embryogenesis were used for conventional breeding. There are still many challenges to face in the process oil palm tissue culture and one of the factors are somaclonal variation. Somaclonal variation was first reported in 1986 that could be identified by fruit mantling and abnormal vegetative growth that led to different result. Malaysian Palm Oil Board (MPOB) and Applied Agriculture Resource (AAR) are the agencies that actively involved in the development of oil palm propagation in Malaysia with many researches and development that has been conducted to produce high yielding clone. They proved that through better management, it could reduce mantling level to less than 5%. Hormone type and the length of culture period become the factor contributed to the clonal abnormalities. This has been countered with the reduction of hormone level and shortens the culture period. The objectives of this review are to identify the factors and effects of somaclonal variation of oil palm and the methods on how to overcome or to improve genetic variation. Through this review, several finding about the method on identification of variation and several MPOB technologies in improving tissue culture has been found out.